Phytochemical analysis and antioxidant activity in leaves of Dodonaea viscosa L.: Phytochemical analysis and antioxidant activity in leaves of Dodonaea viscosa L. - Arunprasath, A (International Journal of Pharmaceutical & Biological Archive, 2018)
The present investigation was focused on the phytochemical screening, Fourier transform-infrared (FT-IR) spectral analysis, and antioxidant activity of Dodonaea viscosa using various organic solvent extracts. Ethanol and petroleum ether leaf extracts from the leaves D. viscosa were tested for the presence of phytochemical constituents, FT-IR analysis, and antioxidant was carried the qualitative analysis of phytoconstituents such as alkaloids, phenols, flavonoids, steroids, tannins, thiols, glycosides, resins, and saponins, and was richly present in petroleum ether and methanolic extracts compared to other extracts. The FT-IR spectrum showed the presence of carbonyls (C=O), phenol (C-O), thioethers (C-S), disulfides (S-S), normal polymeric O-H, phenolic compounds, and arylthio ethers. Plant extracts were screened for the antioxidant activity evaluating their 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical in scavenging ability. The total ascorbic acid content of the extracts was also evaluated. The results revealed that D. viscosa had the best DPPH scavenging activity with a value of ethanolic extract and was better than that of the standard ascorbic acid extract gave the highest ascorbic acid content of D. viscosa.